Effects of short-term ingestion of Russian Tarragon prior to creatine monohydrate supplementation on whole body and muscle creatine retention and anaerobic sprint capacity: a preliminary investigation - Oliver, J. M.; Jagim, A. R.; Pischel, I.; Jäger, R.; Purpura, M.; Sanchez, A.; Fluckey, J.; Riechman, S.; Greenwood, M.; Kelly, K.; Meininger, C.; Rasmussen, C.; et al. (Journal of the International Society of Sports Nutrition, 2014)
Extracts of Russian Tarragon (RT) have been reported to produce anti-hyperglycemic effects and influence plasma creatine (Cr) levels while supplementing with creatine monohydrate (CrM). The purpose of this preliminary study was to determine if short-term, low-dose aqueous RT extract ingestion prior to CrM supplementation influences whole body Cr retention, muscle Cr or measures of anaerobic sprint performance.